Analisis Lingkungan Terhadap Keunggulan Bersaing pada IKM di Bandung, Jawa Barat - Novita Wahyu S. (Majalah Ilmiah Bijak, 2018)
Small and Medium Industry entrepreneurs need to make an understanding of the external environment. Dynamic changes and competition in an industry can find opportunities tailored to the company's capabilities. In addition, external environmental analysis can help entrepreneurs determine the needs and wants of the market. Instead internal environmental analysis shows what the company should do. The purpose of this research is to analyze and know the influence of external environment and internal to competitive advantage.The research method used is survey method, that is descriptive and explanatory survey. The number of respondents in this study were 140 Small and Medium Industry entrepreneurs in Bandung, West Java.Based on the results of research indicate that the external environment and internal environment have an effect on the competitiveness of Small and Medium Industry simultaneously